2008
DOI: 10.1002/bit.21844
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the nitrite pathway using aeration phase length control and step‐feed in an SBR removing nutrients from abattoir wastewater

Abstract: Aeration phase length control and step-feed of wastewater are used to achieve nitrogen removal from wastewater via nitrite in sequencing batch reactors (SBR). Aeration is switched off as soon as ammonia oxidation is completed, which is followed by the addition of a fraction of the wastewater that the SBR receives over a cycle to facilitate denitrification. The end-point of ammonia oxidation is detected from the on-line measured pH and oxygen uptake rate (OUR). The method was implemented in an SBR achieving bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 42 publications
3
67
0
3
Order By: Relevance
“…Interrupting the airflow at a lower DO set-point would therefore result in a greater reduction of the nitrite-oxidizing activity. 39 Significant oxygen savings of up to 43% were achieved in AS3 with respect to AS1. On the other hand, a worsening of the sludge settleability was detected.…”
Section: Operational Strategy 3 (As3)mentioning
confidence: 97%
“…Interrupting the airflow at a lower DO set-point would therefore result in a greater reduction of the nitrite-oxidizing activity. 39 Significant oxygen savings of up to 43% were achieved in AS3 with respect to AS1. On the other hand, a worsening of the sludge settleability was detected.…”
Section: Operational Strategy 3 (As3)mentioning
confidence: 97%
“…In recent years, sequencing batch reactor (SBR) has been successfully employed to remove COD, SS and nutrients from animal wastewaters (Dosta et al, 2008;Lemaire et al, 2008). However, it is reported that the biological technique is often not effective in degrading many antibiotics, for example, sulfonamides, tetracyclines and macrolides (McArdell et al, 2003;Kim et al, 2005;Batt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, partial nitrification to nitrite in continuous reactors might be achieved by switching from the batch start-up into continuous operation. Recently, a number of operational factors for achieving partial nitrification to nitrite have been investigated mainly in SBRs, which demonstrated low DO concentration (Aslan et al 2009;Blackburne et al 2008a;Ye and Zhang 2010), high temperatures (Kim et al 2008), relatively high FA and free nitrous acid (FNA) concentrations Yamamoto et al 2008;Aslan and Dahab 2008), on-line aeration duration control (Guo et al 2009a;Lemaire et al 2008;Antileo et al 2006;Jubany et al 2008;Peng et al 2004;Blackburne et al 2008b), appropriate sludge age (Gee and Kim 2004;Hellinga et al 1998), saline inhibition (Ye et al 2009;Sudarno et al 2010), and periodic anoxic disturbances (Kornaros et al 2010;Kornaros et al 2008) were favorable for selectively inhibiting or limiting the growth of NOB. The control of aeration duration is one of economically feasible methods, since appropriated aeration duration can save the oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%